DISPLACED SUPRACONDYLAR FRACTURES OF HUMERUS IN CHILDREN TREATED WITH OPEN REDUCTION AND CROSS K-WIRE FIXATION - Hussain, Shakir; Ahmad, Malik Faiz; Khan, Khalid, Waqas (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: Results: Conclusion: Open reduction and cross K-wire fixation through a posterior triceps non disturbing approach can be satisfactorily used in the treatment of type III supracondylar fractures that could not be reduced satisfactorily by closed methods. The mean age was 10+6 years. In 3(6%) patients the fracture was flexion and in 47(94%) the fracture was of extension variety. Traditional bone setters were the initial treatment provider for 54% of the patients. The average delay in presentation was 31 hours. Four patients have ipsilateral fractures of the distal radial epiphysis. Postoperatively 9(18%) patients developed pin track infection, and only 2(4%) had transient neuroprexia of the ulnar nerve. This descriptive study was conducted at Orthopaedics Unit District Headquarter Hospital Timergara Dir Lower from December 2005 to September 2008. Fifty children with type III supracondylar fractures, who presented within one week of injury, and in whom satisfactory reduction was not possible by closed means, were evaluated clinically and with radiographs before surgery and at follow up. All these patients underwent open reduction and crossed K-wire fixation through a triceps non disturbing posterior approach. Anatomical reduction of the fracture was achieved and fixation was carried out by two cross Kwires. The patients were regularly followed up and at one the results were measured according to the criteria of Flynn. To describe the outcome of open reduction and cross K-wire fixation through a triceps non disturbing posterior approach used in the treatment of type III supracondylar fractures of humerus in children.